CENP-A nucleosome—a chromatin-embedded pedestal for the centromere: lessons learned from structural biology. Issue 2 (28th July 2020) - Ali-Ahmad, Ahmad; Sekulić, Nikolina
Abstract: The centromere is a chromosome locus that directs equal segregation of chromosomes during cell division. A nucleosome containing the histone H3 variant CENP-A epigenetically defines the centromere. Here, we summarize findings from recent structural biology studies, including several CryoEM structures, that contributed to elucidate specific features of the CENP-A nucleosome and molecular determinants of its interactions with CENP-C and CENP-N, the only two centromere proteins that directly bind to it. Based on those findings, we propose a role of the CENP-A nucleosome in the organization of centromeric chromatin beyond binding centromeric proteins.